Methods to obtain platelet-rich plasma and osteoinductive therapeutic use - Raquel Moreno; Marisa Gaspar Carreño; José Jiménez Torres; José María Alonso Herreros; Ana Villimar; Piedad López Sánchez (Elsevier, 2015)
Introduction: Platelet-Rich Plasma (PRP) is autologous plasma with higher concentration of platelet than basal level, because of an extracting and concentration process. PRP therapeutical use, as osteinductor role, is a controversial issue, due to there are no clinical studies with rigorous design and no firm conclusions can be drawn regarding its uses. Propose: To provide information about methods to obtain PRP, legal considerations about its extraction and use, molecular mechanism of action, as well as available evidence about security and tolerance. Results: PRP can be obtained by manual procedures (opened technique) or disposable kits (closed technique), the latter being medical devices classified as type IIa. AEMPS considers PRP as a drug, establishing some minimum requirements to guarantee safety, traceability, pharmacovigilance and information. PRP provides ideal qualities to play a powerful osteoinductor role to speed up fracture healing or to produce an efficiently and quickly osseointegration of different bone implants, due to the high growth factors content. Infiltration tolerance is generally good, however, it has to be taken into account its great angiogenical potential. Conclusions: In view of its production and application characteristics, PRP is considered as a drug on restricted medical prescription by the AEMPS, so pharmacy department must, at least, supervise its management and handling